Religion and Communication Spaces Journal for Religion, Film and Media - Roger Odin (Journal for Religion, Film and Media, 2015)
Following the reflection initiated in his book The Spaces of Communication, Roger Odin suggests a new distinction between physical communication spaces and mental communication spaces (spaces that we have inside us). The suggestion is exemplified by three film analyses dedicated to the relationships between religion and communication.